HIV-1 Envelope Glycoprotein Cell Surface Localization Is Associated with Antibody-Induced Internalization - Sai Priya Anand; Jérémie Prévost; Jade Descôteaux-Dinelle; Jonathan Richard; Dung N. Nguyen; Halima Medjahed; Hung-Ching Chen; Amos B. Smith; Marzena Pazgier; Andrés Finzi (Viruses, 2021)
To minimize immune responses against infected cells, HIV-1 has evolved different mechanisms to limit the surface expression of its envelope glycoproteins (Env). Recent observations suggest that the binding of certain broadly neutralizing antibodies (bNAbs) targeting the ‘closed’ conformation of Env induces its internalization. On the other hand, non-neutralizing antibodies (nNAbs) that preferentially target Env in its ‘open’ conformation, remain bound to Env on the cell surface for longer periods of time. In this study, we attempt to better understand the underlying mechanisms behind the differential rates of antibody-mediated Env internalization. We demonstrate that ‘forcing’ open Env using CD4 mimetics allows for nNAb binding and results in similar rates of Env internalization as those observed upon the bNAb binding. Moreover, we can identify distinct populations of Env that are differentially targeted by Abs that mediate faster rates of internalization, suggesting that the mechanism of antibody-induced Env internalization partially depends on the localization of Env on the cell surface.